Risk and predictors of severe hyperkalemia after total parathyroidectomy without auto-transplantation in patients with secondary hyperparathyroidism - He, Chenchen; Li, Longfei; Pan, Junhao; Cheng, Guangming; Wang, Chunhui; Tang, Yufu (Frontiers in Endocrinology, 2024)
To identify the risk factors of postoperative severe hyperkalemia after total parathyroidectomy (TPTX) without auto-transplantation in patients with secondary hyperparathyroidism (SHPT).Data on 406 consecutive patients who underwent TPTX without auto-transplantation for secondary hyperparathyroidism at the General Hospital of Northern Theater Command between January 2013 and January 2023, were prospectively collected. Then, patients were divided into the training set (n=203) and the validation set (n=203) in a ratio of 1:1 by timeline. The patients were divided into severe hyperkalemia group and non-hyperkalemia group according to the postoperative serum kalium level >6.0 mmol/L with ECG changes or serum kalium level ≥6.5 mmol/L. Univariate and multivariate logistic regression analyses were used to evaluate the possible risk factors associated with postoperative severe hyperkalemia after TPTX. The predictive performance was evaluated with receiver operating characteristic (ROC) curves with the areas under the ROC curve (AUC) and calibration curve. Decision curve and clinical impact curve analyses were used to validate the clinical application of the value.The incidence of postoperative severe hyperkalemia was 15.5% in all patients, 17.2 % and 13.8% in the training and validation cohorts, respectively. The risk factors associated with postoperative severe hyperkalemia was higher preoperative kalium level. The optimal cut-off value for preoperative serum kalium level was 5.0mmol/L according to the ROC curve. The area under the curve (AUC) achieved good concordance indexes of 0.845 (95%CI, 0.776-0.914) in the training cohort. The sensitivities were 0.829 (95%CI: 0.663-0.934) and 0.857 (95%CI: 0.673-0.960) in the training and validation cohorts, respectively. The specificities were 0.798 (95%CI: 0.729-0.856) and 0.720 (95%CI:0.647-0.785) in the training and validation cohorts, respectively. Calibration curve exhibited a good consistency between actual observations and predicted severe hyperkalemia in the training and validation cohorts.our study found that the preoperative kalium levels is only a risk factor for postoperative severe hyperkalemia in patients undergoing TPTX for secondary hyperparathyroidism. The threshold for preoperative serum kalium levels is 5.0mmol/L that can serve as a useful indicator for identifying patients with severe hyperkalemia after surgery. These results provide valuable suggestion for clinical practice.